Teaching as a Dynamic Phenomenon with Interpersonal Interactions. Issue 2 (17th May 2013) - Watanabe, Katsumi
ABSTRACT: People tend to assimilate toward each other. Importantly, assimilations occur both explicitly and implicitly at various levels, ranging from low‐level sensory‐motor coordination to high‐level conceptual mimicry. Teaching is often confused with simply one means of enhancing learning. However, as we shall see in the other articles in this issue, teaching is a dynamic phenomenon where interpersonal interactions occur explicitly and implicitly at multiple levels. Bonding through coordinated interpersonal interactions occupies a substantial portion of teaching. In this article, I would like to introduce two interpersonal phenomena that exemplify implicit interactions and discuss their relations to the new realization of teaching.